APLIKASI METODE AHP-SWOT UNTUK PERENCANAAN STRATEGILEMBAGA NON PROFIT - Indra Setia Dewi; Arief Daryanto; Idqan Fahmi (Politeknik Negeri Jakarta, 2012)
In this research AHP is used to improve result of SWOT and as a part of SWOT analysis, therefore the method is called A’WOT or AHP-SWOT. Research on the application of AHP-SWOT method in formulating strategic planning was carried out at a constituent based non-profit organization that requires appropriate strategies to face the current dynamics. This organization has had a vision, mission and outline work program but has yet to have an appropriate strategy agreed by its constituentto implement the outline work program. The selection of SWOT method as a basis strategy formulation is a consequence of the form of a constituency based non-profit organization. The board wants the strategic planning organization created involving constituentand agreed by members of the organization. Besides, the constituents of the organization also want to know the strengths, weaknesses, opportunities and threats affecting the continuity of the organization. For that purpose the SWOT method is used in conjunction with AHP method to facilitate the management of organizational decisions on formulated strategies. The research object in this study is a constituency-based non-profit organization that develops forest management certification system in Indonesia is namely the Indonesian Ecolabelling Institute (LEI). Keywords: Strategic planning, non-profit, SWOT, AHP, LEI